The mediatization of contemporary violence: the case of Nahir Galarza in Argentina - Rovner, Rocío (Comunicación y Género [Communication and Gender], 2021)
This research is about the case of Nahir Galarza, a young Argentine woman who was sentenced to life imprisonment, on the charge of murdering her ex-boyfriend, Fernando Pastorizzo. The methodological proposal involves an analysis of the media circulation of the case, from the time it becomes public until the conviction; at the intersection with a theoretical reflection on violence against women, gender, the mass media and digital media. The results show that this event was crossed by multiple factors, evidenced in speeches that constructed predominant meanings, within the framework of a hetero – patriarchal system sustained by the media, institutions and their daily violence.
Keywords: mediatization; violence; gender; institutions; massive media